A sensitive colorimetric DNA biosensor for specific detection of the HBV gene based on silver‐coated glass slide and G‐quadruplex‐hemin DNAzyme. Issue 4 (29th November 2017) - Li, Yubin; Liu, Sheng; Deng, Qiujuan; Ling, Liansheng
Abstract : A sensitive colorimetric DNA biosensor for specific detection of single stranded oligonucleotide (ssDNA) is proposed in this paper. The biosensor is based on silver‐coated glass (SCGS) and G‐quadruplex‐hemin DNAzyme. Capture DNA is immobilized on the surface of SCGS by Ag—S bond. Signal DNA can be used to hybridize with the target DNA which is selected from the Hepatitis B virus(HBV) gene as target HBV DNA, and the HRP‐mimicking G‐quadruplex‐hemin DNAzyme can be formed through the function of a guanine‐rich fragment from signal DNA to catalyze the oxidation of 2, 2‐azinobis(3‐ethylbenzothiozoline)‐6‐sulfonicacid (ABTS 2– ) by H2 O2 . The reaction will be monitored along the side of absorbance changes at 418 nm and it can be viewed by naked eye with the change of color as well. Upon addition of target Hepatitis B virus(HBV) DNA, signal DNA could bind on the surface of SCGS, and the concentration of G‐quadruplex‐hemin DNAzyme immobilizing on the surface of SCGS is depended on that of target HBV DNA. Under the optimum conditions, the absorption was proportional to the concentration of target HBV DNA over the range from 0.5 to 100 nM, with a detection limit of 0.2 nM. In addition, the biosensor is target specific and practicability. This assay might open a new avenue for applying in the diagnosis of HBV disease in the future.